Mental Logic and the Denials of Conjunctions and Disjunctions - Miguel López-Astorga (Trans/Form/Ação, 2016)
ABSTRACT: The mental models theory predicts that, while conjunctions are easier than disjunctions for individuals, when denied, conjunctions are harder than disjunctions. Khemlani, Orenes, and Johnson-Laird proved that this prediction is correct in their work of 2014. In this paper, I analyze their results in order to check whether or not they really affect the mental logic theory. My conclusion is that, although Khemlani et al.'s study provides important findings, such findings do not necessarily lead to questioning or to rejecting the mental logic theory.